Novgorod's Political Development in 1456-1470 - Manusadžianas, Tomas (Lietuvos istorijos studijos, 1999)
This article is the first part of a work - 'Novgorod at the political cross-roads before annexation to Moscow' (1456-1478). The work deals with a situation of Novgorod's choice of political dependence between Moscow and Lithuania during the last period of Novgorod's independence.In the article, there is presented an introductory part of the mentioned work - foreword and objectives of the work. The conception of Novgorod political development (1456-1478), 'prehistory' of the subject, and the chronological period of 1456-1470 are also discussed.From the second half of the XIII century to the middle of the XV century, Novgorod belonged to the political system of the Vladimir Moscow Grand Duke practically without interruptions and rejected rare attempts of involvement in a Lithuanian political system.During the period of 1456-1470, Novgorod made no attempts to leave the subordination of the Vladimir Grand Duke. Lithuania also overtly didn't try to include Novgorod in its own political system - Lithuanian dukes in Novgorod had traditional status of 'service dukes.' Conclusively, the situation of the choice of political dependence didn't take place in the period.
Keywords: -